RADEC Learning Model: Practicum to Enhance Students' Science Process Skills on Temperature and Heat - Mubarokiyah, Tasya Azizah; Aripin, Aripin; Rizal, Rahmat (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This study aims to analyze the implementation of the RADEC learning model with practicum method in enhancing students' science process skills on temperature and heat material. The method used in this research is quasi-experiment with nonequivalent control group design. The study was conducted at MA Negeri 1 Tasikmalaya with a research population of 263 students across 8 classes of XI MIPA. Purposive sampling technique was used to select the sample, resulting in XI MIPA 5 as the experimental group and XI MIPA 3 as the control group. To measure students' science process skills, pretest and posttest in the form of reasoned multiple-choice questions were administered, totaling 12 items representing 6 basic science process skill indicators on temperature and heat material. Data analysis techniques included expert validation, instrument testing, analysis of science process skills mastery, analysis of learning model feasibility, N-Gain analysis, prerequisite tests, and hypothesis testing. The hypothesis testing results using t-test at a significance level (? = 0.05) showed that after the implementation of the RADEC learning model with practicum method, tobserved > tcritical, specifically 3.43 > 1.67, thus rejecting H0 and accepting Ha. Therefore, with 95% confidence level, it can be concluded that the application of the RADEC learning model with practicum method effectively enhances students' science process skills on temperature and heat material. From this research, the RADEC learning model with the practicum method can be the choice of learning model applied in Physics learning and as a means of practicing for students in improving science process skills.